2003
DOI: 10.1080/0014013032000121642
|View full text |Cite
|
Sign up to set email alerts
|

In-vehicle vibration study of child safety seats

Abstract: SummaryThis paper reports experimental measurements of the in-vehicle vibrational behaviour of stage 0&1 child safety seats. Road tests were performed for eight combinations of child, child seat and automobile. Four accelerometers were installed in the vehicles and orientated to measure as closely as possible in the vertical direction; two were attached to the floor and two located at the human interfaces. An SAE pad was placed under the ischial tuberosities of the driver at the seat cushion and a child pad, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…The results of these studies can be found, among others in [19][20][21]. The results of the crash tests presented, among others in the works [22][23][24] showed that improper fastening of the child in the seat may cause additional injuries.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…The results of these studies can be found, among others in [19][20][21]. The results of the crash tests presented, among others in the works [22][23][24] showed that improper fastening of the child in the seat may cause additional injuries.…”
Section: Introductionmentioning
confidence: 98%
“…Much work and research has been devoted to examining the frequencies of vertical vibrations transmitted from the rear seat vehicle and seat to the child's body. Examples can be found, among others in the works [28][29][30]. The suspension of the vehicle is an important aspect in considering the issue of passenger comfort.…”
Section: Introductionmentioning
confidence: 99%
“…Whole-body vibration measurement has been done on baby car seat and prenatal incubator ([7]- [8]). However, there is no research has been carried out for whole-body vibration on baby hammock.…”
Section: Introductionmentioning
confidence: 99%
“…The whole-body vibrational behaviour of small children is of relevance towards the design of systems such as child safety seats. Vibrational measurements for child seats were first reported by Giacomin (2000 and2003) who measured acceleration at the interface between child and child seat in automobiles while driving. The same author has also experimentally measured the whole-body apparent mass of a group of eight small children (Giacomin 2004).…”
Section: An Important Information Thatmentioning
confidence: 99%